The problematical of spatial differences in the distribution of population and equipments in the space of the area of Constantine and reality of reorganization - Fareh , Mohamed Ikbal; Mahrezi, Mohamed Kameleddine (Journal of Human Sciences, 2021)
The aim of this publishing is the problematical placing of the spatial differences in the breaking down of the population as well as the distribution of the equipments through the space of the area of Constantine. In fact‚ according to its historical importance and its demographic weight‚ numerous equipments lie within this area and are distinguished by their non-homage- neatly leading to the emergence of local differences‚ and consequently to flagrant disparities between the chief towns and their spaces from where the necessity to develop these zones and to consider the breaking down of the population in order to relieve the downtowns and to create a balance in terms of breaking down of the population and the distribution of equipments among the communes.